Fusarium Wilt of Canary Island Date Palm - Monica L. Elliott (EDIS)
Unlike most fungal diseases of palms, this disease is very host specific, with the primary host being Phoenix canariensis (Canary Island date palm). It is caused by Fusarium oxysporum f. sp. canariensis. The name “Fusarium wilt of Canary Island date palm” was given to this disease to distinguish it from two other Fusarium wilt diseases that occur on palms, which are also very host specific. In Florida (and the U.S.), the name is often shortened to simply “Fusarium wilt.” This document is PP-215, one of a series of the Plant Pathology Department, UF/IFAS Extension. Original publication date January 2006.